Sufism in the secret history of Persia - Milani, Milad; Cambridge eBooks (Durham : Acumen Publishing, 2013)
Sufism formed one of the cultures of resistance which has existed in the social fabric of Persia since antiquity. Such resistance continues to manifest itself today with many looking to Sufism as a model of cooperation between East and West, between traditional and modern. Sufism in the Secret History of Persia explores the place of Sufi mysticism in Iran's intellectual and spiritual consciousness through traditional and contemporary Sufi thinkers and writers. Sufism in the Secret History of Persia examines the current of spirituality which extends from the old Iranian worship of Mithra to modern Islam. This current always contains elements of gnosis and inner knowing, but has often provided impetus for socio-political resistance. The study describes how these persisting pre-Islamic cultural and socio-religious elements have secretly challenged Muslim orthodoxies and continue to shape the nature and orientation of contemporary Sufism.
Title from publisher's bibliographic system (viewed on 02 Oct 2015).
Keywords: Sufism -- Iran -- History; Electronic books